An economic analysis of the role of traditional craft institutions in promoting tourism: A case study of Ghardaïa- Algeria - Lamine, Chara; Belkacem, Benatallah (International journal of economic perspectives, 2025)
This study aims to highlight the current state of traditional handicrafts in the Wilaya of Ghardaïa as one of the sectors that serve as a potential attraction for tourists of various types, and to explore its role in stimulating tourism activity in the region. This is particularly relevant in light of tourism being regarded as a multifaceted industry closely linked to other economic activities. The study presents statistics related to local artisans in Ghardaïa, as well as data on tourist arrivals to the region over the past four years. The findings indicate that traditional handicrafts contribute significantly to the promotion of both domestic and international tourism.